What is Veiling? - Sahar Amer (Edinburgh Edinburgh University Press, 2014)
Examines the practice of veiling in Muslim culture, discussing its history, its religious, social, and political significance, and its importance to both conservative and progressive Muslim women as a symbol of commitment to their beliefs. --Publishers description.
Include Index, Bibliography, Notes and Illustration
Keywords: Hijab (Islamic clothing) -- Veils--Religious aspects--Islam -- Muslim women--Clothing